2018
DOI: 10.1111/jsr.12703
|View full text |Cite
|
Sign up to set email alerts
|

Poor self‐reported sleep quality and health‐related quality of life in patients with chronic fatigue syndrome/myalgic encephalomyelitis

Abstract: Non-restorative sleep is a hallmark symptom of chronic fatigue syndrome/myalgic encephalomyelitis. However, little is known about self-reported sleep disturbances in these subjects. This study aimed to assess the self-reported sleep quality and its impact on quality of life in a Spanish community-based chronic fatigue syndrome/myalgic encephalomyelitis cohort. A prospective cross-sectional cohort study was conducted in 1,455 Spanish chronic fatigue syndrome/myalgic encephalomyelitis patients. Sleep quality, fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 39 publications
1
18
0
Order By: Relevance
“…The ndings in the present study are in broad agreement with previous studies, which have reported that poor sleep quality was associated with poorer health status, disease severity, impaired daily activities, and reduced survival [24,25]. This study acts as a reminder to enquire about sleep quality in patients with the operation and consider investigation and treatment for potentially treatable cause, including measures to improve factors that adversely affect sleep.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The ndings in the present study are in broad agreement with previous studies, which have reported that poor sleep quality was associated with poorer health status, disease severity, impaired daily activities, and reduced survival [24,25]. This study acts as a reminder to enquire about sleep quality in patients with the operation and consider investigation and treatment for potentially treatable cause, including measures to improve factors that adversely affect sleep.…”
Section: Discussionsupporting
confidence: 92%
“…The observed distributions in the insomnia were summarized in de ned groups based on the scores from ISI as follows: none (0-7), mild (8)(9)(10)(11)(12)(13)(14), moderate (15)(16)(17)(18)(19)(20)(21), severe (22)(23)(24)(25)(26)(27)(28). Depression was rate on PHQ-9 of ve levels: none (0-4), mild (5-9), moderate (10)(11)(12)(13)(14), moderatesevere (15)(16)(17)(18)(19) severe (20)(21)(22)(23)(24)(25)(26)(27). Anxiety was graded according to the score of the GAD-7: none (0-4), mild (5-9), moderate (10-13), moderate-severe (14-18), severe (19)(20)(21).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have provided strong evidence for autonomic nervous system (ANS) involvement in individuals with CFS/ME, including perturbations in the structure and function of brain (reflected by fMRI testing) [4][5][6][7][8][9][10][11]. In brief, cerebral blood flow volume changes and reduced HRV may lead to greater exacerbation of ANS symptoms in individuals with CFS/ME.…”
Section: Introductionmentioning
confidence: 99%
“…These data were consistent with those from the CFS assessment. Poor sleep quality was widely reported in patients with CFS [16], and nocturia was associated with poor sleep quality [17,18]. In our study, we observed a signi cantly (P < 0.01) improved frequency of nocturia in the subjects of the product group (data not shown).…”
Section: Discussionmentioning
confidence: 40%